2017
DOI: 10.3847/1538-3881/aa9332
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Scalable Gaussian Process Modeling with Applications to Astronomical Time Series

Abstract: The growing field of large-scale time domain astronomy requires methods for probabilistic data analysis that are computationally tractable, even with large datasets. Gaussian Processes are a popular class of models used for this purpose but, since the computational cost scales, in general, as the cube of the number of data points, their application has been limited to small datasets. In this paper, we present a novel method for Gaussian Process modeling in one-dimension where the computational requirements sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
494
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 792 publications
(496 citation statements)
references
References 102 publications
2
494
0
Order By: Relevance
“…It is possible to model these oscillations using sinusoidal functions or wavelets, as done by other authors (i.e., Deming et al 2012;Kovács et al 2013;von Essen et al 2014). However, we decided to use the Gaussian process code celerite (Foreman-Mackey et al 2017) to fit these pulsations nonparametrically. Gaussian processes treat the pulsations as a form of correlated noise whose properties are described by a parameterized covariance matrix fitted to our data.…”
Section: Noise Modelmentioning
confidence: 99%
“…It is possible to model these oscillations using sinusoidal functions or wavelets, as done by other authors (i.e., Deming et al 2012;Kovács et al 2013;von Essen et al 2014). However, we decided to use the Gaussian process code celerite (Foreman-Mackey et al 2017) to fit these pulsations nonparametrically. Gaussian processes treat the pulsations as a form of correlated noise whose properties are described by a parameterized covariance matrix fitted to our data.…”
Section: Noise Modelmentioning
confidence: 99%
“…Our simple harmonic oscillator Gaussian process model consists of three main components: two Q 1 2 = terms, which are commonly used to model granulation in asteroseismic analyses (Harvey 1985;Huber et al 2009;Kallinger et al 2014), and one Q 1  term, which has been shown to describe stellar oscillations effectively (Foreman-Mackey et al 2017), to describe the envelope of the stellar oscillation signal. The resonant frequency 0 w of this component is thus an independent estimate of max n , and we compare our asteroseismic max n measurement made from the analysis in the frequency domain to the max n we generate here through a pure time domain analysis.…”
Section: Gaussian Process Transit Modelsmentioning
confidence: 99%
“…Furthermore, what is most interesting for our case is that some of the possible celerite kernels are well suited to describe different forms of stellar variability. According to equation 49 in Foreman-Mackey et al (2017), the kernel for a stochastically driven, damped harmonic oscillator with a quality factor (Q ) larger than 0.5 is given by…”
Section: Gaussian Process Regressionmentioning
confidence: 99%